Profile of tuberculosis and its response to anti-TB drugs among tuberculosis patients treated under the TB control programme at Felege-Hiwot Referral Hospital, Ethiopia - Zenebe, Yohannes (BMC Public Health, 2016)
BACKGROUND: Tuberculosis (TB) is a global concern for both developing and developed countries. Currently it becomes more complex due to increasing levels of drug resistance and HIV co-infection. Delayed diagnosis and high case load are major factors contributing to continued transmission and failure to the treatment outcome. The study was conducted to determine the profile and treatment outcomes of TB patients at Felege-Hiwot Referral Hospital. METHODS: We analyzed the records of 1761 TB patients registered for treatment in Felege Hiwot Referral Hospital from July 2010 to June 2015. Data on patients’ socio-demographic characteristics, type of TB, HIV status and treatment outcome were analysed. Descriptive statistics and binary logistic regression models were used to present data. The odds ratio and the 95 % confidence intervals were calculated. A p-value of < 0.05 was considered statistical significant. RESULTS: The proportion of smear positive, smear-negative and extra-pulmonary TB were 205 (11.6 %), 548 (31.1 %) and 1008 (57.2 %), respectively. The overall treatment success rate accounts 542(80.8 %) with unsuccessful treatment of 129(19.2 %). The treatment outcome varied by the years from 68.9 to 97.4 %. Among tuberculosis patients, 459(26.1 %) of them were HIV positive. Being HIV positive (AOR = 4.29, 95 % CI, 2.20–8.37 P = 0.001), retreatment (AOR = 5.32, 95 % CI, 1.92–14.3, P = 0.001), rural residency (AOR = 18.0, 95 % CI, 9.06–37.82, P = 0.001) and the age group of 15–24 years (AOR = 2.91, 95%CI, 1.00–8.45, P = 0.04) showed statistical significant association for poor treatment outcome. CONCLUSIONS: In the studied region, the overall treatment success rate was still below the WHO target of success rate, 85 %. However, the trend of treatment success rate showed a promising increment. Patients at high risk of unsuccessful treatment outcome should be identified early and given additional follow-up, medical intervention and social support.